FACTORS AFFECTING AGRICULTURAL TEACHERS’ WORK ATTITUDE IN SELECTED SECONDARY SCHOOLS: A CASE OF ABEOKUTA-SOUTH AND SAGAMU LOCAL GOVERNMENT AREAS, OGUN STATE, NIGERIA - Ayinde, A. F. O.; Bolarinwa, K. K.; Sanusi, R. A.; Ajao, H. O. (FUDMA JOURNAL OF SCIENCES, 2023)
This study assessed the relationship between agricultural teachers’ socioeconomic characteristics and their work attitude. A structured questionnaire was used to elicit information from a total of 96 agricultural teachers in selected secondary schools in Abeokuta South and Sagamu Local Government Areas of Ogun State, through a multi-stage sampling procedure. The data collected were subjected to descriptive, Pearson Product Moment Correlation (PPMC) and Chi square analyses. Results indicated that 61.3% of the agricultural teachers were females, with modal (49.6%) age between 41 and 50 years. Majority (73.0%) were married and 59.1% held the position of class teacher. In terms of work attitude, results showed that agricultural teachers exposed students to both theory and practical aspects of agriculture ( = 4.53 SD= 0.58) and at times used local languages to drive home important points ( =4.24, SD =0.87). Also, results revealed significant association between agricultural teachers’ work attitude and their sex (r = -0.230, p<0.05), teaching experience (r = -0.217, p<0.05), income (r = 0.255, p<0.05) grade level (r = -0.237, p<0.05) as well as position (r = 0.215, p<0.0). The major constraints affecting optimum performance of respondents were absence of well-equipped laboratory ( =2.37, SD = 0.83) and inadequate incentives ( =2.05, SD = 0.03) among others. The study concluded that agricultural teachers work attitude in the study area was affected by their socio-economic and work-related characteristics. The study recommended among others that the State government should provide adequate incentives for agricultural teachers in order to further excel in their duty.